Pendekatan Sistem Pembelajaran Di UPT SMP Negeri 27 Medan - Dina Oktavia; Irma Tussa’diah Hasibuan; Khoirun Nisa; Maulidayani Maulidayani (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This article discusses the learning systems approach. One approach that can be used to determine. The quality of the educational process is a systems approach. Through systems approach, can be seen various aspects that influence the success of a process. Learning is referred to as a system because it contains components which are interrelated and influence each other. Teachers, students, materials, Methods, media, facilities and infrastructure are components contained in learning. Availability and the effectiveness of each of these components is then determined will determine the success of learning. And the type of research method used is qualitative research where the data we take is based on observation, interviews and documentation.